Kesiapan Berwirausaha Warga Binaan Lembaga Pemasyarakatan Wanita Melalui Pendidikan Kewirausahaan Dan Self-Efficacy - Aspiannor, Akhmad (LPPM Universitas Ekasakti, 2024)
This research aims to examine the influence of entrepreneurship education and self-efficacy on the entrepreneurial readiness of inmates at the Martapura Class IIA Women's Penitentiary. The sample consists of 86 individuals who have undergone entrepreneurship education or training at the Martapura Class IIA Women's Penitentiary. The first hypothesis states that entrepreneurship education has a significant influence on entrepreneurial readiness, with a t-value of 5.319 > 1.666 at a significance level of 0.000 < 0.05. The second hypothesis states that self-efficacy has a significant influence on entrepreneurial readiness, with a t-value of 4.564 > 1.666 at a significance level of 0.000 < 0.05. The third hypothesis states that entrepreneurship education and self-efficacy together have a significant influence on entrepreneurial readiness, with an F-value of 41.444 > F-table 3.09 at a significance level of 0.000 < 0.05. This research indicates that entrepreneurship education and self-efficacy have a positive and significant impact on the entrepreneurial readiness of inmates at the Martapura Class IIA Women's Penitentiary